Herbal Cosmetics: “Trends in Skin Care Formulation” - Ashawat, M.S.; Banchhor, Madhuri; Saraf, Shailendra; Saraf, Swarnlata (Pharmacognosy Reviews)
Popularity of herbal cosmetics in society and technological advances in manufacturing process has resulted in flooding of market with herbal formulations. Recently herbal cosmetics have gained much recognition and became popular among people. These products claimed to have efficacy and intrinsic acceptability due to routine use in daily life and devoid of side effects commonly seen with synthetic products. The herbs used in preparation of these Skin cosmetics have multifunctionality like antioxidant, antiinflammatory, antiseptic and antimicrobial. This paper will review the sate of art of herbal based skin cosmetic formulations along with scientific data and concerned cosmetic importance of herbs that could be utilized in preparation of these formulations.
Keywords: Herbal Cosmetics; Skin Cosmetics; Antioxidant; Anti-inflammatory; Antiaging